2012
DOI: 10.1016/j.compositesa.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Particle simulation for predicting fiber motion in injection molding of short-fiber-reinforced composites

Abstract: This study proposes a numerical analysis for predicting fiber motion during injection molding of short-fiber-reinforced composites using the moving particle semi-implicit (MPS) method. Its meshless and Lagrangian nature enables us to track individual fibers and to easily represent free surfaces. In this study, the mechanism of fiber orientation in a T-shaped bifurcation was investigated experimentally and numerically. The fiber orientation of injection-molded glass-fiber/polypropylene composite was observed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…The distance between the particles was 0.15 mm; the single fiber was modeled as a rigid body composed of 10 particles (fiber aspect ratio was 10), and the initial position of the fiber was vertical to the plates. 20 The densities of the fluid and fiber were 900 kg/m 3 and 1500 kg/m 3 , respectively.
Figure 3.The SPH analytical model of a single fiber in the simple shear flow.
…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The distance between the particles was 0.15 mm; the single fiber was modeled as a rigid body composed of 10 particles (fiber aspect ratio was 10), and the initial position of the fiber was vertical to the plates. 20 The densities of the fluid and fiber were 900 kg/m 3 and 1500 kg/m 3 , respectively.
Figure 3.The SPH analytical model of a single fiber in the simple shear flow.
…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, the important influences of the heterogeneous distribution and fiber accumulation during the injection molding process may not take into consideration. To address these ignored influences, Yashiro et al 19,20 have predicted the injection molding process of SFRP composites using a meshless method called moving particle semi-implicit (MPS). Several injection molding models with different geography were analyzed, and the motion of individual fibers can be followed since the specific fibers were modeled.…”
Section: Introductionmentioning
confidence: 99%
“…Londoño‐Hurtado et al found that the Folgar–Tucker model can predict the fiber orientation, and presented a mathematical model to model orientation distribution in the processing of fiber‐reinforced composites. Yashiro et al developed a numerical method for predicting fiber motion during injection molding of short fiber‐reinforced composites by the moving particle semi‐implicit method. And they numerically investigated the fiber orientation mechanism of the T‐shaped bifurcation with the meshless and Lagrangian nature of the method.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, knowing the flow induced fiber orientation is of great importance because the fiber orientation state significantly affects the composite mechanical properties. Accordingly, accurate and efficient predictions of the fiber orientation are challenging tasks and have been investigated for many years owing to their industrial applications .…”
Section: Introductionmentioning
confidence: 99%